The Spellmans strike again [large type] - Lutz, Lisa (Lutz, Lisa. Spellman novel., 2010)
At the ripe old age of thirty-two, former wild child Isabel 'Izzy' Spellman has finally agreed to take over the family business, but the transition won't be a smooth one. First among her priorities as head of Spellman Investigations is to dig up some dirt on the competition, slippery ex-cop Ricky Harkey. Next, faced with a baffling missing-persons case, Izzy hires an actor friend to go under-cover as a butler. Meanwhile, Izzy is being blackmailed by her mother into going on blind dates. At Spellman headquarters, it's business as usual.